Measuring CD Pit Spacing with a Laser: Applying Fundamental Physics Principles and the Diffraction Grating Method - Naufal, Muhammad Risyad; Rodhiyah, Marathur (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aimed to measure the distance between data pits on a Compact Disc (CD) by utilizing its reflective surface as a diffraction grating. When a laser beam strikes the CD, the alternating pits and lands create a diffraction pattern of bright and dark fringes. The pit spacing can then be determined from this pattern and compared with literature values. Methodology: A red laser was used as the light source, and the resulting diffraction pattern was analyzed using simple Python code based on the diffraction principle. This approach provides an efficient and low-cost method to perform quantitative analysis using readily available tools. Main Findings: The measured distance between pits on the Compact Disc was 1.607 ± 0.017 µm, with an accuracy error of 0.004%. The results closely matched reported literature values, though slight deviations may have arisen from parallax errors, the difficulty of identifying the laser’s exact reflection point, or ruler precision. From these results, it can be seen that a simple basic physics experiment can easily performed by students because the equipment and procedures are simple yet still produce good results. Novelty/Originality of this study: This work demonstrates that meaningful physics experiments can be conducted with everyday materials and simple instruments, offering a time- and cost-efficient way to explore fundamental concepts such as diffraction. The study highlights the potential of using familiar objects like compact discs to make physics learning more engaging and accessible for students and young researchers.